Ikoniczność: podobieństwo i „tertium comparationis" - Tabakowska, Elżbieta (Przestrzenie Teorii, 2007)
The paper analyses the phenomenon of iconicity in relation to its significance for literary theory. One of the key notions in modern philosophy of language and linguistics, iconicity is seen as a motivated interrelation beween form and meaning. In this, it is akin to mimesis - one of the basic concepts in theory of literature. Based on similarity, iconicity requires a conscious presence of an observer, who discovers and states the existence of similarity by reference to a tertium comparationis. It occurs as an effect of a mental process, as an interface bewteen semantics (the level of conventionalized meaning) and pragmatics (the level of contextual modifications of meaning). Thus it is intrinsically subjective: a representation of things as seen by a cognizant mind. Defined as a similarity between a conceptual structure and a linguistic form created by the mind, iconicity is manifested as sequentiality, proximity or quantity of elements; it is either imagic or diagrammatic. As a property of all texts and all discourse, it blurs the traditional distinction between "literary" and "non-literary" uses of language: the difference reduces to one of quantity, which "literatury" being characterised by a larger quantity of motivated interrelationships combined with a lower level of their conventionalization. The author concludes by claiming that - like mimesis - iconicity may be profitably discussed in terms of Roland Langacker's notion of subjectification, with the tertium comparationis present in the mind rher than in the external reality.